Research Progress on the Pharmacological Effects and Clinical Application of Erigeron Brevicapas in the Treatment of Malignant Tumors - Chen, Kun; Zhao, Yanli; Ou, Ju (Journal of Contemporary Medical Practice, 2025)
To investigate the pharmacological action and clinical application of Breviscapus and its derivatives in the treatment of malignant tumors, and to provide reference for further research and clinical application of breviscapus and its derivatives in the treatment of malignant tumors. In China National Knowledge Network (CNKI), WanfangDate Data Knowledge Platform and PubMed database with "Breviscapine", "Pharmacology", "Oncology", "Breviscapine", "scutellain", "Pharmacology", "Tumor" and so on as keywords, Relevant literatures published from May 2000 to August 2022 were retrieved to sort out and summarize the pharmacological effects and clinical applications of calendula breviscapus in tumor therapy.